Learning Rotation using the Context of Palembang Songket Fabric Motif for 3rd Grade Secondary School - Sari, Arika; Putri, Ratu Ilma Indra; Susanti, Ely (Mathematics Education Journal, 2023)
Rotation is an essential part of geometric transformations. This research aims to produce a learning trajectory of rotation material and determine the role of activities in learning the rotation which is expected to be able to support students understanding the concept of rotation learning in grade IX. The approach used is Pendidikan Matematika Realistik Indonesia (PMRI) with Lesson Study for Learning Community (LSLC) as learning system. The method used in this research is a design research type validation study. This research was conducted in limited face-to- fece meetings at secondary school number 1 Palembang during the pandemic and involved 13 students of class IX. The data were collected using video recordings and photos taken during the learning process, student interviews, student work, discussion results, and field notes at each meeting. The results of this study indicate that the learning trajectory can support the informal to formal concept of rotation, including the activity of recording the starting point and endpoint, analyzing and interpreting changes of starting and endpoints using one’s language, and writing the rotation formula. Therefore, it can be concluded that a series of activities by exploring the Palembang songket fabric motif plays a role in helping students understand the concept of rotation easily and allows them to produce rational imaginations and fun learning. DOI: https://doi.org/10.22342/jpm.17.2.17447.189-208